Proposed treatment strategy for reactive hypoglycaemia - Younes, Younes R.; Cron, Nicholas; Field, Benjamin C.T.; Nayyar, Vidhu; Clark, James; Zachariah, Sunil; Lakshmipathy, Kavitha; Isuga, Jimboy O.; Maghsoodi, Negar; Emmanuel, Julian (Frontiers in Endocrinology, 2024)
Background/Aim: Managing reactive hypoglycaemia (RH) poses challenges due to limited and often ineffective treatment options. We report a case series and draw on this to propose a stepwise treatment approach consisting of lifestyle modifications, metformin, GLP-1 analogues, and the use of flash glucose monitoring technology.Method: A retrospective review was conducted to analyse the management of 11 cases presenting with recurrent RH symptoms.Result: Two patients experienced successful resolution of symptoms through lifestyle modifications.Metformin alone was effective in treating seven out of nine patients who received pharmacological treatment. Two patients with previous upper gastrointestinal surgery showed a partial response to metformin and benefited further from additional long-acting GLP-1 analogue. Pharmacological intervention led to significant reductions in insulin and C-peptide levels during mixed meal tolerance tests (P-values 0.043 for insulin and 0.006 for C-peptide). Finally, flash glucose monitoring technology was useful in early detection and preventing episodes of hypoglycaemia in one of these patients with persistent symptoms.These findings highlight the potential efficacy of escalated treatment strategies for RH, including the use of metformin, GLP-1 analogues, and flash glucose monitoring technology.